Ultrasound-Guided Transvaginal Aspiration and Sclerotherapy for Uterine Cystic Adenomyosis: Case Report and Literature Review - Zhao, Xinxin; Yang, Ye (Frontiers in Medicine, 2022)
Background: Uterine cystic adenomyosis is a very rare type of adenomyosis which can be easily misdiagnosed in clinical practice. In the past, cases have been mostly treated with surgical resection of the uterine lesion. Case presentation: We report the case of a 25-year-old woman who presented with severe dysmenorrhea for more than 1 year. Physical examination showed that the uterus was enlarged. The transvaginal ultrasound showed a cystic mass of about 5.0x3.6x3.6 cm in the posterior myometrium, with dense echo spots and no blood flow signal in the cystic part. Magnetic resonance imaging (MRI) indicated hemorrhages within the cystic mass, suggesting the possibility of uterine cystic adenomyosis. The lower abdominal pain and severe dysmenorrhea were not alleviated after a 6-month trial of oral contraceptives. Subsequently, she underwent ultrasound-guided transvaginal aspiration and sclerotherapy for uterine cystic adenomyosis. Approximately 90 mL of chocolate-colored fluid was aspirated from the mass and 20 mL of lauromacrogol was injected in the cyst. The reduction rates of the mass 3 and 12 months after the procedure were 92.01% and 99.10%, respectively. Her dysmenorrhea completely resolved. One and half year after the operation, she had a successful pregnancy and gave birth to a healthy baby through vagina. Conclusion: The rare entity of uterine cystic adenomyosis can be treated safely and effectively by ultrasound-guided transvaginal aspiration and sclerotherapy.